A mental health focus to amplify climate resilience actions - Jyoti Mishra; Hahrie Han; Veerabhadran Ramanathan (npj Climate Action)
Abstract As the climate crisis worsens, it is an urgent imperative to protect both people and ecosystems and advance resilience. Building climate resilience requires three pillars: (1) mitigation actions to reduce climate risks; (2) adaptation measures to reduce exposure and vulnerability and thus survive unavoidable risks; and (3) change in societal behaviors or societal transformation to create a sustainable future for all. The physical health hazards of the climate crisis have been a prominent driving force to advance resiliency efforts, and health co-benefits of mitigation and adaptation actions are being actively monitored and communicated. Indeed there is evidence for major global environmental regulations that have been enacted thus far on air pollutants and ozone depleting chemicals, all based on their health impacts. Here, we emphasize the chronic impacts of the climate crisis on mental health, and posit that adding a focus on mental health and well-being is important for advancing climate resilience. We highlight the mental health co-benefits of mitigation and adaptation and illustrate the importance of supporting mental health for societal behavioral transformation. Specifically, we discuss how mental health is essential to societal transformation actions, including (a) climate education for all; (b) greater social connection, particularly within the most climate vulnerable frontline communities; (c) intentional coalition building across key sectors, including scientists, medical professionals, as well as community and faith leaders that value mental health, well-being and spiritual health; and (d) long-term policymaking that prioritizes both environmental sustainability and human wellbeing.